The Road to a Robust and Affordable SiC Power MOSFET Technology - Hema Lata Rao Maddi; Susanna Yu; Shengnan Zhu; Tianshi Liu; Limeng Shi; Minseok Kang; Diang Xing; Suvendu Nayak; Marvin H. White; Anant K. Agarwal (Energies, 2021)
This article provides a detailed study of performance and reliability issues and trade-offs in silicon carbide (SiC) power MOSFETs. The reliability issues such as threshold voltage variation across devices from the same vendor, instability of threshold voltage under positive and negative gate bias, long-term reliability of gate oxide, screening of devices with extrinsic defects by means of gate voltage, body diode degradation, and short circuit withstand time are investigated through testing of commercial devices from different vendors and two-dimensional simulations. Price roadmap and foundry models of SiC MOSFETs are discussed. Future development of mixed-mode CMOS circuits with high voltage lateral MOSFETs along with 4−6× higher power handling capability compared to silicon circuits has been described.